2020
DOI: 10.1002/nop2.652
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors affecting stress among nurses providing care at COVID‐19 isolation hospitals at Egypt

Abstract: Aims To examine predictive factors affecting stress among nurses providing care at COVID‐19 Isolation Hospitals at Egypt. Methods A cross‐sectional study conducted in five Isolation governmental hospitals for COVID‐19. 374 nurses included at the study. Characteristic forms, factors affecting nurses’ stress and Nursing Stress Scale (NSS) were used to collect data. Results (52.1%) of studied nurses had moderate level of total nursing stress sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
1
30
0
3
Order By: Relevance
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence according to the month of data collected was as follows: February: 32% ( n = 14; 95% CI 25–41; I2 = 98), March: 45% (n = 6; 95% CI 37–53; I2 = 96) and April: 50% ( n = 13; 95% CI 35–66; I2 = 98). Seventeen studies [ 20 , 35 , 36 , 39 , 43 , 44 , 46 , 54 , [57] , [58] , [59] , [60] , [61] , [62] , [63] , 67 , 69 ] involving nurses who were working on the frontline showed stress prevalence at 46% (95% CI = 39–54; I 2 = 97), whereas 20 studies including mixed nurses working in the frontline and second line showed the stress prevalence was 42% (95% CI = 31–53, I 2 = 99). Thirteen studies that used the Perceived Stress Scale (PSS) showed a pooled prevalence of stress at 50% (95% CI = 41–59, I 2 = 98), whereas eight studies [ 35 , 45 , [54] , [55] , [56] , 63 , 64 , 67 ] using the Impact of Event Scale-Revised (IES-R) had a pooled prevalence of 50% (95% CI = 37–63, I 2 = 99).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, their symptoms of stress have been positively associated with female gender, aged ≤ years, watching or reading COVID-19 news ≥ two hours per day, poor family and social support (10), fear of infection, fear transmission to the family member. Furthermore, it has been negatively associated with having training courses on COVID-19, availability of personal protective equipment and obtaining special attention from hospital administration (11).…”
mentioning
confidence: 99%
“…These results supported with the study conducted by (Mohammed et al, 2020), who reported that around three-quarter of nurses were female and only less than one quarter enrolled at training courses. Also, a cohort with the study performed by (Hendy et al, 2020), who detected that mean age of studied nurses was 32.06 ± 3.90 and about two-thirds of them were female.…”
Section: Statistical Designmentioning
confidence: 96%